TINJAUAN HUKUM ISLAM TENTANG PRAKTIK JUAL BELI BAWANG MERAH DENGAN SISTEM TAKSIRAN: Studi Kasus di Desa Larangan Kecamatan Larangan Kabupaten Brebes - Tugimin; Irvan Iswandi; Ahmad Asrof Fitri (Jurnal Penelitian Multidisiplin Ilmu, 2023)
Is motivated by the researcher’s curiosity about the practice of buying and selling shallots with an estimation system when it is viewed based on Islamic law in Larangan Village. Larangan District, Brebes Regency, it is due to the practice of sale and purchase transactions of shallot harvest using an estimation system. The research method used was field research which was descriptive in nature, the research was carried out by collecting data through direct observation in the field, observation, interviews with people who were directly involved in this activity and also the documentation of activities. Based on the results of the research conducted, it pointed out that the practice of buying and selling shallots using the estimation system in the village of Larangan was a legitimate buying and selling transaction due to it has adjusted with the buying and selling principle, namely the existence of a seller and a buyer, the existence of sale and purchase agreement and the existence of goods or services that are the object of the transaction. This transaction was a valid habit (urf) and it did not contradict with the religious teachings. Moreover, in theory of muamalah reveals that everything is permissible as long as there are no arguments that against it. Besides, the practice of buying and selling using this estimation system was also legitimate based on in fiqh that the essence of commerce or buying and selling is mutual willingness between transacting parties.